1969 - September 1995 (Newton Lower Falls, Mass., 1995)
Comprehensive indexed bibliography with selected abstracts of the world's economic literature (over 300 major economic journals and collected volumes) compiled from the American Economic Association's Journal of economic literature and the Index of economic articles in journals and collective volumes. Over 90% of the articles are in English or include English summaries.
Keywords: Kinh tế,Economics; Tạp chí định kỳ